Batik Jetis as a Local Wisdom Market Concept in Porong Market, Sidoarjo Regency - Ni'mah, Meilinda Zahrotun; Graha, I Made Satya; Revana, Dano Quinta (Jurnal Planologi, 2025)
The Type A traditional market in Porong Subdistrict, Sidoarjo Regency, still has facilities that do not meet standards, such as limited parking areas, unseparated entry and exit points, non-functional reweighing stations and security posts, and a lack of basic fascilities such as toilets, hand washing stations, and trash bins. This condition does not align with the provisions of Ministry of Home Affairs Regulation No. 21 of 2021 and SNI 8152:2021, which require the presence of various supporting facilities such as an administrative office, breastfeeding rooms, health rooms, places of worship, fire suppression systems, and waste and clean water treatment facilities. This study aims to evaluate the condition of market facilities based on these two regulations and formulate a restructuring strategy to improve market quality. The method used is quantitative descriptive with an Importance Performance Analysis (IPA) approach, involving 96 market visitor respondents. The results show that six sub-variables fall under the High Priority category: parking area, toilets, handwashing stations, trash bins, security posts, and vehicle access. These findings serve as the basis for formulating a market revitalization plan rooted in local wisdom, integrating the cultural elements of Batik Jetis as the regional identity. This study is expected to contribute to socio-cultural urban planning through a traditional market revitalization model that not only improves facility quality but also supports the preservation of local culture and promotes economic growth for the community in Sidoarjo Regency.